Pengaruh Lingkungan Kerja Fisik Dan Komunikasi Terhadap Kinerja Karyawan Pada PT Multi Jasa Grup Kota Tangerang - Fahreza, Hafidz; Wardani, Windy Gustia (CV. KAMPUS AKADEMIK PUBLISING, 2026)
The purpose of this study is to determine the effect of Physical Work Environment and Communication on Employee Performance at PT Multi Jasa Grup, both partially and simultaneously. This study employs a quantitative method with an associative research approach. The results of the T-test show that the Physical Work Environment variable has no significant effect on Employee Performance, with a significance value of 0.361 > 0.05 and a t-count value of 0.922 < t-table 2.006. Meanwhile, the Communication variable has a significant effect on Employee Performance, with a significance value of 0.001 < 0.05 and a t-count value of 5.861 > t-table 2.006. The results of the F-test indicate that simultaneously, the Physical Work Environment and Communication have a positive and significant effect on Employee Performance, with a significance value of 0.001 < 0.05 and an F-count value of 35.490 > F-table 3.18. The Coefficient of Determination test shows an Adjusted R Square value of 0.561 or 56.1%, meaning that the Physical Work Environment and Communication simultaneously contribute 56.1% to Employee Performance, while the remaining 43.9% is influenced by other factors outside the research model. Therefore, it can be concluded that communication plays an essential role in improving employee performance, while the physical work environment does not have a significant impact. Hence, the company needs to strengthen its internal communication system to create effective coordination and support higher employee productivity.